If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1(3x + -8) = 8 Reorder the terms: 1 + -1(-8 + 3x) = 8 1 + (-8 * -1 + 3x * -1) = 8 1 + (8 + -3x) = 8 Combine like terms: 1 + 8 = 9 9 + -3x = 8 Solving 9 + -3x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3x = 8 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 8 + -9 -3x = 8 + -9 Combine like terms: 8 + -9 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 6b^2-12b-58=0 | | y=5cos^2x+3 | | z^2+2z-2i+1=0 | | (sinx+1)(cosx-2)=0 | | 3n^2-6n-9=0 | | 0.57=logx | | 3n^2+12n-90=-8 | | k^2-4k-60=0 | | 9x+9y+18=0 | | 6y-3=5-2y | | 7x-14=-7x | | 66-(4x+12)=4(x+9)+x | | 10-5x=2(5x-10) | | 0.03x+0.05(2000-x)=99.5 | | 22x-23Y=21 | | 4=6x-3+7 | | e^5x-1=12 | | 24+5y=9y | | 8x+3(2x-1)=5x+6 | | 22=2w-8 | | 3(x-4)=5(x-6) | | K-9=-11 | | 4x+5(5/2)=15 | | 1-2(x-1)=x+6 | | -12=2+h | | 4(-3)+5y=15 | | -9w+3= | | 3x-5(0)=8 | | 3(1)-5y=8 | | 4x-9y=-15 | | 5+4.5= | | 2x^2-3bx+b^2=0 |